Polymorphism of microsatellite markers linked with Rf1 and Pl5/Pl8 loci in sunflower Helianthus annuus L. - Yu. I. Karabitsina; N. V. Alpatieva; E. B. Kusnetsova; V. A. Gavrilova; N. V. Titov; E. E. Radchenko; I. N. Anisimova (Биотехнология и селекция растений, 2022)
Background. Microsatellite (SSR) markers are an effective tool for certifying collections of plant genetic resources, as well as for identifying genes that determine valuable biological and agronomic traits. The knowledge of their polymorphism is important for characterizing genetic diversity within the sunflower (Helianthus annuus L.) collection. The present study was aimed at analyzing nucleotide polymorphism of SSR-markers linked with the genes for fertility restoration (Rf1) and downy mildew resistance (Pl5/Pl8). Materials and methods. The material included 84 self-pollinated lines of VIR sunflower genetic collection, F1 and F2 hybrids from crosses between fertile lines VIR 365 and RIL130, and offspring from test crosses. Polymorphism of SSR markers ORS224, ORS511, ORS799 and НА4011 was studied by means of PCR analysis. To determine the microsatellite structure and variability, the amplified fragments were cloned and sequenced. Results. The unique alleles which differed from the typical ones (characteristic for most genotypes) were revealed in the ORS224 marker locus of four lines, and the unique alleles in the ORS511 locus were observed in 10 lines. The ORS511 unique allele of line VIR 365 included two 161 and 240 bp fragments, while line RIL130 was characterized by a typical 159 bp fragment. The profiles of typical and unique markers were inherited as allelic variants of the same locus in F2 of (VIR 365 × RIL130) and a population from VIR 111A × (VIR 365 × RIL130). The nucleotide sequences of unique alleles differed from typical allelic variants in the length and number of repeat units (GA in ORS224 and AT/GT in ORS511), and also by the presence of indels and nucleotide substitutions. Differences in length of НА4011 marker 240 and 200 bp allele variants were caused by 80, 47 and 44 bp indels. Conclusions. A number of lines in the VIR sunflower genetic collection are marked by the unique alleles of microsatellite loci ORS224 and ORS511, which differ from the frequently occurring variants in the length and number of repeat units, as well as in the presence of indels and nucleotide substitutions. Polymorphism of allele variants of HA4011 microsatellite is associated with the presence of indels of 80, 47 and 4 bp.